Sosialisasi Aplikasi Mobile Untuk Sistem Antrian Pada Puskesmas Sako Kota Palembang - Nurhajar Anugraha; Aryanti Aryanti; Dyah Utari Yusa Wardhani; Pertiwi Nurul Utami; Imas Ning Zhafarina; Muhammad Hanif Fatin; Diah Novita Sari; Yulia Hapsari; Adhelia Febriasari Harahap (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
This Community Service Activity aims to provide knowledge about mobile applications for queuing systems that are expected to make it easier for patients who will check their health or seek treatment at the Health Center. The methods used in this activity include interview methods with the Health Center to find out the source of the problem that is the basis for this community service activity. Furthermore, a socialization method is carried out, where in this socialization activity an explanation will be given to both the Health Center and patients about the use of the application that will be designed. The results of this activity are socialization regarding the Mobile application for the patient queuing system along with socialization of the procedures for using the application. Where after the implementation of this activity is carried out, the application that will be designed will make it easier for patients and patients no longer need to sit and queue for a long time when going to the Sako Health Center for treatment.